STUDY OF TOTAL CHOLESTEROL (TC), TRIACYLGLYCEROLS (TG), HIGH DENSITY LIPOPROTEIN CHOLESTEROL (HDL-C) IN TYPE II DIABETES MELLITUS.â€ - ANITA P MANDARE,; NEELAM DEOKAR,; Patil, Smita V; Gaikwad Pandurang B, (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: There are probably 100 million people in the world with diabetes mellitus (DM), and incidences of diabetes are on the rise. Dyslipidemia is one of the common disorders which are seen in most of the diabetes patients, which causes cardiovascular disorders. The aim of this study is to investigate the total cholesterol (TC), triacylglycerols (TGs), high-density lipoprotein cholesterol (HDL-C) in Type 2 DM, and healthy controls. Methods: The study was conducted on 50 controls and 50 Type 2 diabetic subjects between age group of 30 and 60 years. Serum TC was determined by an enzymatic (cholesterol oxidase/phenol-aminophenazone [PAP]) colorimetric method and TGs were determined by an enzymatic (glycerol phosphate oxidase-PAP) method, and HDL-C was estimated by a precipitant method. Statistical analysis was done using unpaired t-test. Results: The mean value of TC, TGs, and HDL-C in normal subjects is 165.5±24.24, 118.7±41.58, 28.38±7.85 mg/dl, respectively, and the value of TC, TGs, and HDL-C in diabetic patients is 179±31.69, 164.35±27.93, 25.4±6.86 mg/dl, respectively. The observed difference in the means of TC, TGs, and HDL-C in normal and diabetic are statistically significant (p<0.05). Conclusion: From the present study, it is concluded that TC, TGs, and HDL-C levels for all persons with Type 2 DM should be done as a routine test. Furthermore, early diagnosis and treatment of dyslipidemia can be used as a preventive measure for the development of cardiovascular disease in Type 2 diabetes. Keywords: Diabetes mellitus, Dyslipidemia, Lipid profile, Total cholesterol, Triglycerides, High-density lipoprotein cholesterol.